ANALISIS STRUKTUR ATAS PASCA GEMPA BANGUNAN BERTINGKAT KANTOR WALI NAGARI MALAMPAH KABUPATEN PASAMAN - Fransisko Fransisko; Deddy Kurniawan; Elfania Bastian (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
In general, the upper structure includes beams, columns, floor plates which function to support the loads acting on a building. Calculations that will be carried out on the construction of the Wali Nagari Malampah Office are floor slabs, beams and columns. Structural loads (dead loads, live loads) are based on SNI 03-2847:2002 and earthquake loads are based on SNI 03-1726:2019, where the portal is calculated and modeled using the SAP2000 program. The purpose of this calculation is to get an overview of the basic principles of planning and reviewing the building structure, comparing the results of the author's calculations with the results of the planning consultant's calculations. From the calculation results, the largest moment in beam B2 is 64.8586 kN-m and the largest moment in column K1 (40 x 40 cm) is 8.4235 kN-m. For floor slabs, there are differences in reinforcement, namely: floor slab thickness of 120 mm, reinforcement 10-150 mm for the x direction and y direction of the author, floor slab 120 mm, reinforcement 10- 250 mm for the x direction and y direction of the planner, column K1( 40 x 40 cm) 16 D 19 and column K2 (30 x 30 cm) 8 D 19 (same as the planner), For beams B1 and B2 there are differences in dimensions and reinforcement, namely: beam B1 (30 x 45 cm) 4 D 19 authors , block B1 (30 x 50 cm) 5 D 19 planner, for beam B2 (25 x 40 cm) 4 D 19 (same as planner).Keywords: Upper structure, Reinforcement, Sap 2000